‘FAILURE’ AS A SPACE OF CRITIQUE AND IMAGINATION: THE CASE OF FACIAL RECOGNITION TECHNOLOGIES - Cruz Lobato, Luisa; Lima, Thallita (AoIR Selected Papers of Internet Research, 2026)
Facial recognition (FR) has been promoted worldwide as a modern security solution. In Brazil, its expansion has taken place experimentally, through unregulated pilot projects and opaque public-private partnerships. With its widespread, fast implementation, errors and failures became evident: wrongful arrests, technical flaws, systemic biases. These failures are advocated as integral to the bettering of the technology and thus tolerated. Our work explores the critical spaces that these failures produce. Inspired by biometrics artworks, we show that grappling with the failures of FR allows for a mode of experimentation that privileges both critique and alternative modes of interrogating and imagining the world.